Productivity, quality, and nutrient uptake of intensive forage crop rotations based on corn in sandy soil (northern Morocco) - Hassane Sidikou, Abdel Aziz; Drissi, Saad; Bouaziz, Ahmed; Dhassi, Khalid; Amlal, Fouad; Darrhal, Nassima; Bamouh, Ahmed; El Hajli, Hicham; Alouatir, Zakia; Ait Houssa, Abdelhadi (Universitas Sebelas Maret, 2023)
Intensive dairy farming systems in the sandy soil of northwestern Morocco are based on three successive forage crops per year, including corn. The aim was to evaluate the productivity and the quality of different intensive crop successions based on corn in sandy soil. Three forage crops per year (winter, spring, and summer cropping seasons) were tested according to six successions: 1. fallow-corn-corn, 2. oat-corn-corn, 3. berseem-corn-corn, 4. pea/triticale-corn-corn, 5. oat-soybean-corn, and 6. berseem-corn-soybean. Each succession of crops was evaluated in two years field experiment using a randomized complete block design. Results revealed that oat-corn-corn and pea/triticale-corn-corn successions produced the highest dry biomass (46.5 t ha-1 year-1). The crop succession of berseem-corn-soybean resulted in the lowest biomass (30.8 t ha-1 year-1). The highest net energy for lactation was recorded at oat-corn-corn and pea/triticale-corn-corn successions (303 103 MJ ha-1 year-1). The crop successions based on one corn (oat-soybean-corn and berseem-corn-soybean) recorded the lowest net energy for lactation (195.5 103 MJ ha-1 year-1). The oat-corn-corn, pea/triticale-corn-corn, and oat-soybean-corn successions recorded the highest crude protein values (3.9 t ha-1 year-1). Soil organic matter and the content of soil on total N, P, and Mg were similar for the different crop successions at the end of the experimental years.